An Analysis of Students' Creative Thinking Abilities Middle School Class VIII on Consonance Material: Analisis Kemampuan Berfikir Kreatif Siswa SMP Kelas VIII Pada Materi Kesebangunan - Maryanti, Tia; Nuryadi, Nuryadi (Jurnal Sains dan Teknologi (JSIT), 2024)
This research aims to describe the creative thinking abilities of students at SMP Negeri 1 Sedayu on Awakening material using descriptive methods. The sample in this study was 31 students in class VIII of SMP Negeri 1 Sedayu, even semester of the 2023/2024 academic year. The instruments used in this research were descriptive tests to obtain data on students' creative thinking abilities and interviews to complement and strengthen information originating from administering tests on congruence material that had been empirically validated. To see students' creative thinking abilities, 4 indicators are used, namely 1). Fluency (Fluency); 2) Flexibility; 3) originality (originality); 4). Elaboration (Elaboration). The data analysis technique used in this research is percentage analysis. Based on the analysis of data obtained for fluency indicators of 28%, flexibility of 23%, originality of 23%, and elaboration of 27%.